Ingestion of lodged foreign bodies in the stomach and duodenum: about 6 observations solved surgically - Estefan, Alberto; Chifflet, Juan (Cirugía del Uruguay, 1972)
Extraneous bodies swallowed by patients and their gastroduodenal topography constitute the subject of this paper. Their most important characteristics and possible complications are. described from the point of view of their surgical treatment; operatory indications are set forth. Case material i.ncludes 6 patients